Ibuprofen loaded PVA/chitosan membranes: A highly efficient strategy towards an improved skin wound healing - Morgado, Patrícia Isabel da Cruz (2018)
During wound healing, an early inflammation can cause an increase of the wound size and the healing process can be considerably belated if a disproportionate inflammatory response occurs. (S)-ibuprofen (IBP), a non-steroidal anti-inflammatory agent, has been used for muscle healing and to treat venous leg ulcers, but its effect in skin wound healing has not been thoroughly studied thus far. Herein, IBP-β-cyclodextrins carriers were designed to customise the release profile of IBP from poly(vinyl alcohol)/chitosan (PVA/CS) dressings in order to promote a faster skin regeneration. The dressings were produced using supercritical carbon dioxide (scCO2)-assisted technique. In vitro IBP release studies showed that β-cyclodextrins allowed a controlled drug release from the hydrogels which is crucial for their application in wound management. Moreover, the in vivo assays revealed that the presence of PVA/CS membranes containing IBP-β-cyclodextrins carriers avoided scab formation and an excessive inflammation, enabling an earlier skin healing.